2011
DOI: 10.1038/nmeth.1682
|View full text |Cite
|
Sign up to set email alerts
|

Toward the blood-borne miRNome of human diseases

Abstract: In a multicenter study, we determined the expression profiles of 863 microRNAs by array analysis of 454 blood samples from human individuals with different cancers or noncancer diseases, and validated this 'miRNome' by quantitative real-time PCR. We detected consistently deregulated profiles for all tested diseases; pathway analysis confirmed disease association of the respective microRNAs. We observed significant correlations (P = 0.004) between the genomic location of disease-associated genetic variants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
309
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 326 publications
(318 citation statements)
references
References 18 publications
6
309
1
2
Order By: Relevance
“…A prior power analysis has demonstrated that these cohort sizes at an alpha error probability of 0.05 and a statistical power of 0.95 require an effect size of below 1.2. In previous studies, we usually discovered miRNAs with respective power and these miRNAs were frequently successfully validated by real-time PCR (14,15).…”
Section: Samplesmentioning
confidence: 99%
“…A prior power analysis has demonstrated that these cohort sizes at an alpha error probability of 0.05 and a statistical power of 0.95 require an effect size of below 1.2. In previous studies, we usually discovered miRNAs with respective power and these miRNAs were frequently successfully validated by real-time PCR (14,15).…”
Section: Samplesmentioning
confidence: 99%
“…Extracellular miRNA functions are varied, and include relaying signals between cells and modulating angiogenesis, neurogenesis, cell proliferation and apoptosis, among others [10]. Changes in composition and concentration of miRNA in the extracellular compartment are in many cases related to pathological processes ongoing in the body, which may allow them to be used in some cases as biological markers of disease activity [11].…”
Section: Characteristics Of Extracellular Mirnamentioning
confidence: 99%
“…Los miRNA pueden encontrarse en el suero humano y pueden ser biomarcadores debido a su alta homogeneidad y estabilidad 15,16 . Inicialmente se identificó que los mecanismos de transporte y liberación de estas moléculas se dan mediante la formación y liberación de exoxomas que se producen por una vía dependiente de ceramidas 17 .…”
Section: Micrornasunclassified